Getting Things Done, Virtually! - The Role of Virtual Team Leadership in Virtual Team Effectiveness - E, Jude Ashmi (Ushus Journal of Business Management, 2017)
A virtual team’s success depends on the team’s effectiveness. Accomplishing such a team’s effectiveness is far more difficult when compared with traditional work teams. This article is a result of an exploratory study of the role of leadership in virtual teams. Virtual teams’ leadership is seemingly situational and supervisory, depending on the task. This study reveals that (1) individual virtual team members act as leaders based on the specific requirements for getting things done, (2) classifies virtual team leadership under supervisory and facilitating leadership, (3) suggests that both leadership roles are essential for virtual team effectiveness and functioning and (4) recommends exploration of leadership-oriented communication competency, shared understanding and virtual team citizenship behaviour as these are required for the effective performance of a virtual team.